2022
DOI: 10.1111/cote.12656
|View full text |Cite
|
Sign up to set email alerts
|

Eco‐friendly approach on wool pretreatment and effect on the wool structure and dyeability

Abstract: This research investigated the effect of various proteolytic enzymatic pretreatment on morphological and chemical features and the dyeability properties of wool fibres. Scoured merino wool fibres are treated with protease, papain, trypsin, and pepsin in specified conditions. Each enzyme activity measurement was provided by appropriate methods such as Bradford, BAPNA (N-benzoyl-1-arginine-p-nitroanilide), and BSA (Bovine Serum Albumin). Enzymatic processes were carried out for 24 h in the incubator set at 40 C,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…14,19 Compared with the existing enzyme treatment studies, the protease catalytic system process is characterized by high efficiency, short treatment time, ease of operation, and can be processed continuously. [29][30][31][32] Its treatment efficiency is similar to the traditional chlorination treatment, and the shrinkage prevention effect is better than that of chlorination treatment. 32 Furthermore, it has the characteristic of ecological safety.…”
Section: Shrink Resistance and Mechanical Propertiesmentioning
confidence: 99%
“…14,19 Compared with the existing enzyme treatment studies, the protease catalytic system process is characterized by high efficiency, short treatment time, ease of operation, and can be processed continuously. [29][30][31][32] Its treatment efficiency is similar to the traditional chlorination treatment, and the shrinkage prevention effect is better than that of chlorination treatment. 32 Furthermore, it has the characteristic of ecological safety.…”
Section: Shrink Resistance and Mechanical Propertiesmentioning
confidence: 99%
“…Breeding for white wool has always been a priority in sheep farming, due to the high level of pursuit by the textile industry [1,3,5,8,9]. And, with the rise of green concept [3,10,11], natural colored wool is a way to replace traditional printing and dyeing [12]. A comparison of modern and ancient wool products reveals a reduction in the diversity of modern wool colors [5,13], making it imperative to conserve colored wool breeding resources.…”
Section: Introductionmentioning
confidence: 99%
“…The subject of two articles in this special issue is an examination of the effects of enzymatic processes on various properties of wool fibres, including dyeability. Dr. Gizem Ceylan Türkoğlu and her colleagues, 1 and Ms. Berrak Buket Avcı and Dr. Gökhan Erkan, 2 from Dokuz Eylül University, Turkey, demonstrate the results of pretreatment with protease and glucose oxidase enzymes, respectively. In both studies, it was revealed that enzymatic pretreatment increased dye uptake and resulted in a higher colour yield than the untreated samples.…”
mentioning
confidence: 99%